Replication Data for: A comparison study of five different methods to measure carotenoids in biofortified yellow cassava (Manihot esculenta) - Jaramillo Valencia, Angélica M.; Londoño Hernandez, Luis Fernando; Orozco, Juan Camilo; Patiño, Gelver; Belalcázar, John Eiver; Davrieux, Fabrice; Talsma, Elise F. (2018)
The most commonly used method for measuring carotenoid concentration is high-performance liquid chromatography (HPLC). Nevertheless, easier, quicker, and less costly proxy methods exist. We aimed to determine the diagnostic performance of several proxy methods: the spectrophotometer, iCheck Carotene, and near-infrared spectroscopy using both a desktop (dNIRS) and a portable (pNIRS) device for the measurement of total carotenoid concentration (TCC) and all-trans-β-carotene concentration (trans-BC) in 30 fresh cassava (Manihot esculenta Crantz) storage roots in comparison with HPLC. The spectrophotometer presented the highest predictability for TCC, followed by iCheck, dNIRS, and pNIRS. The dNIRS showed the highest predictability and agreement for trans-BC. The pNIRS showed the poorest repeatability and greatest underestimations compared with HPLC. The agreement between all methods was lower for higher carotenoid concentration, with the exception of the spectrophotometer. According to our results, and for screening purposes, the measurement of carotenoids in fresh cassava roots can be carried out by spectrophotometer, iCheck Carotene and NIRS methods depending on the availability of equipment